Miracles of the Virgin in medieval England : law and Jewishness in Marian legends - Williams Boyarin, Adrienne, 1976- (D.S. Brewer, 2010)
Legendary accounts of the Virgin Mary's intercession were widely circulated throughout the middle ages, borrowing heavily, as in hagiography generally, from folktale and other motifs; she is represented in a number of different, often surprising, ways, rarely as the meek and mild mother of Christ, but as bookish, fierce, and capricious, amongst other attributes. This is the first full-length study of their place in specifically English medieval literary and cultural history. While the English circulation of vernacular Miracles of the Virgin is markedly different from continental examples, this book shows how difference and miscellaneity can reveal important developments within an unwieldy genre. The author argues that English miracles in particular were influenced by medieval England's troubled history with its Jewish population and the rapid thirteenth-century codification of English law, so that Mary frequently becomes a figure with special dominion over Jews, text, and legal problems. The shifting codicological and historical contexts of these texts make it clear that the paradoxical sign"Mary" could signify in both surprisingly different and surprisingly consistent ways, rendering Mary both 'mediatrix' and 'legislatrix'. Adrienne Williams Boyarin is Assistant Professor of English at the University of Victoria (British Columbia).